Physiological analysis reveals the mechanism of accelerated growth recovery for rice seedlings by nitrogen application after low temperature stress - Wang, Hui; Zhong, Lei; Fu, Xiaoquan; Huang, Shiying; Zhao, Desheng; He, Haohua; Chen, Xiaorong (Frontiers in Plant Science, 2023)
Low temperature and overcast rain are harmful to directly seeding early rice, it can hinder rice growth and lower rice biomass during the seedling stage, which in turn lowers rice yield. Farmers usually use N to help rice recuperate after stress and minimize losses. However, the effect of N application on the growth recovery for rice seedlings after such low temperature stress and its associated physiological changes remain unclearly. Two temperature settings and four post-stress N application levels were used in a bucket experiment to compare B116 (strong growth recovery after stress) with B144 (weak growth recovery). The results showed that the stress (average daily temperature at 12°C for 4 days) inhibited the growth of rice seedlings. Compared to the zero N group, the N application group’s seedling height, fresh weight and dry weight significantly increased after 12 days. In particular, the increases in all three growth indicators were relatively higher than that of N application at normal temperature, indicating the importance of N application to rice seedlings after low temperature stress. The antioxidant enzyme activity of rice seedlings increased significantly after N application, which reduced the damaging effect of ROS (reactive oxygen species) to rice seedlings. At the same time, the soluble protein content of seedlings showed a slow decrease, while the H2O2 and MDA (malondialdehyde) content decreased significantly. Nitrogen could also promote nitrogen uptake and utilization by increasing the expression of genes related to NH4+ and NO3- uptake and transport, as well as improving the activity of NR (nitrate reductase) and GS (glutamine synthetase) in rice. N could affect GA3 (gibberellin A3) and ABA (abscisic acid) levels by regulating the anabolism of GA3 and ABA. The N application group maintained high ABA levels as well as low GA3 levels from day 0 to day 6, and high GA3 levels as well as low ABA levels from day 6 to day 12. The two rice varieties showed obvious characteristics of accelerated growth recovery and positive physiological changes by nitrogen application after stress, while B116 generally showed more obvious growth recovery and stronger growth-related physiological reaction than that of B144.